Re-treatment With Adjuvant Radioactive Iodine Does Not Improve Recurrence-Free Survival of Patients With Differentiated Thyroid Cancer - Bouvet, Clément; Barres, Bertrand; Kwiatkowski, Fabrice; Batisse-Lignier, Marie; Chafai El Alaoui, Meryem; Kauffmann, Philippe; Cachin, Florent; Tauveron, Igor; Kelly, Antony; Maqdasy, Salwan (Frontiers in Endocrinology, 2019)
Introduction: Loco regional persistence or recurrence of differentiated thyroid cancer (DTC) is frequent despite initial thyroidectomy and radioactive iodine therapy (RAI). The aim of this study was to analyze the impact of a complementary adjuvant RAI (Ad-RAI) on disease recurrence following re-operation on patients with locally persistent or recurrent DTC. Patients and Methods: A retrospective study of 85 patients with DTC was conducted. All patients were initially treated with total thyroidectomy and RAI, and re-operated for a locally persistent or recurrent disease. Propensity score was calculated to predict the impact of Ad-RAI on survival after reoperation, and to reduce the bias of the limited sample size and the prognostic tests. Results: 49 (58%) patients were re-treated with Ad-RAI after re-operation while 36 (42%) were only followed up. Disease recurrence after re-treatment (re-operation ± Ad-RAI) was detected in 31 patients (36.5%). In multivariate analysis, age >55 years (HR: 3.9 [1.6; 9.5]; p < 0.00001) was the main poor prognostic factor for recurrence-free survival. Three parameters independently influenced the decision to administer ad-RAI: low number of previous RAI administrations, Nx before re-operation, and pTg > 30 μg/l. These parameters were incorporated in the Propensity score calculation. If ad-RAI tended to improve recurrence-free survival (median survival 17.4 vs. 10.9 months), adjustment using the Propensity score removed any difference between the groups (p = 0.54), confirming the limited value of ad-RAI. Conclusion: In patients with locally persistent or recurrent DTC, age is the main independent prognostic factor. Adjuvant RAI does not improve recurrence-free survival of DTC patients.